A Case of Unilateral Drop Foot As A Result of Long Duration Crouch - Akgöl, Gürkan; Çelikbağ, Bahar (Fırat University, 2012)
In this case we diagnosed peripheric nevre compression by means of clinical findings and electrophysiological studies. There was unilateral postural type nerve compression due to long time squatting in this patient. We started vitamin B therapy, physiotherapy and follow up.

Bu olguda peroneal sinir yaralanması görülen hastada klinik bulgular ve elektrofizyolojik çalışmalar ile periferik sinir sıkışması tanısı kondu. Hastada uzun süre çömelmeye bağlı tek taraflı postural tipte sıkışma vardı. Vakaya B vitamini başlandı ve fizik tedavi uygulanarak takibe alındı.
Uzun Süre Çömelme Sonucu Oluşan Tek Taraflı Düşük Ayak Olgusu